Follicle-stimulating hormone receptor autoantibody associated primary ovarian insufficiency successfully treated with corticosteroids: a case report - Carrie Riestenberg, M.D; Susan Ahern, D.O; Mousa Shamonki, M.D (Elsevier, 2020)
Objective: To report a case of successful controlled ovarian stimulation (COH) for oocyte cryopreservation in a patient with autoimmune primary ovarian insufficiency (POI) and polyglandular autoimmune syndrome (PGAS) type 2. Design: Case report. Setting: Private in vitro fertilization clinic. Patient(s): 25-Year-old woman, G0, with autoimmune POI and PGAS type 2. Intervention(s): Diagnosis of autoimmune interference with FSH signaling, with subsequent high-dose corticosteroid immune suppression and successful oocyte cryopreservation. Main Outcomes Measure(s): Successful stimulation with exogenous gonadotropins, oocyte retrieval, and cryopreservation. Result(s): Retrieval and cryopreservation of 36 metaphase-II (MII) oocytes. Conclusion(s): Scrutiny of POI cases will facilitate identification of a subset of patients in whom immune suppression with short-term, high-dose corticosteroids may enable successful COH.